Estudo da frequência da mutação BRAF p.V600E em nevos melanocíticos e melanomas mucosos orais - Taynara Asevedo Campos de Resende (2021)
Melanocytic nevi are benign neoplasms derived from melanocytes. Common cutaneous acquired melanocytic nevus is frequently in human skin and it has a higher incidence in the third decade of life. Although a low rate of malignant transformation is estimated, a portion of cutaneous melanoma is preceded by a melanocytic acquired nevus. BRAF p.V600E somatic mutation activates the MAPK/ERK pathway and cell proliferation. It is implicated in the cutaneous melanocytic acquired common nevus pathogenesis and cutaneous melanoma that arise in sites not chronically sun-exposed. After melanoma molecular description, its therapeutic was improved by Braf and Mek inhibitors. Oral mucosal acquired melanocytic nevus (NMO) and oral mucosal melanoma (MMO) are rare lesions with uncertain pathogenesis. There is scanty literature about NMOs molecular features and few studies on MMOs. Most articles are series that evaluate mucosal melanomas from several sites collectively. In the present study, BRAF p.V600E mutation was assessed in 14 intramucosal NMOs and 7 primary MMOs, excluding lip samples, by allele specific quantitative polymerase chain reaction (AS-qPCR). A narrative literature review had been performed to calculate BRAF p.V600E frequency in NMOs and MMOs. Original articles in English language were included, since it was possible to identify the primary sample site and mutational status, by sample or its frequency. Data about patient age, country, type of tumor (primary, recurrent or metastatic) and sequence technique used also were collected. Five in fourteen NMOs samples (35.7%) analyzed in the present study were BRAF p.V600E positive and three in seven MMOs samples (42.8%) showed the mutation. In the narrative literature review, added to our results, 19 NMOs were evaluated and 8 NMOs presented BRAF p.V600E mutation, corresponding to a frequency of 42.1%. Between 374 MMOs evaluated, 24 MMOs showed the mutation totalizing the frequency of 6.4%. In conclusion, BRAF p.V600E oncogenic mutation was assessed in NMOs and MMOs samples. Additionally, in combination with the literature review, it calculated the mutation frequency in NMOs and MMOs, improving the molecular characterization of those lesions.